Switch from IL-5 to IL-5-Receptor α Antibody Treatment in Severe Eosinophilic Asthma - Drick N; Milger K; Seeliger B; Fuge J; Korn S; Buhl R; Schuhmann M; Herth F; Kendziora B; Behr J; Kneidinger N; Bergmann KC; et al. (Journal of Asthma and Allergy, 2020)
Nora Drick,1,* Katrin Milger,2,* Benjamin Seeliger,1 Jan Fuge,1 Stephanie Korn,3 Roland Buhl,3 Maren Schuhmann,4 Felix Herth,4 Benjamin Kendziora,5 Juergen Behr,2 Nikolaus Kneidinger,2 Karl-Christian Bergmann,5 Christian Taube,6 Tobias Welte,1 Hendrik Suhling1 1Department of Respiratory Medicine, Hannover Medical School, Hannover, Germany; 2Department of Internal Medicine V, Ludwig-Maximilians University of Munich (LMU), Munich, Germany; 3Pulmonary Department, Mainz University Hospital, Mainz, Germany; 4Department of Pneumology and Critical Care Medicine, Thoraxklinik, University of Heidelberg, Heidelberg, Germany; 5Allergy-Centre-Charité, Charité – Universitätsmedizin Berlin, Berlin, Germany; 6Department of Pulmonary Medicine, University Hospital Essen – Ruhrlandklinik, Essen, Germany*These authors contributed equally to this workCorrespondence: Hendrik Suhling Email suhling.hendrik@mh-hannover.deBackground: Anti-IL-5 antibodies represent an established therapy for severe eosinophilic asthma (SEA), but some patients show inadequate response. The objective of this study was to assess the effects of a switch to anti-IL-5Rα therapy in patients with inadequate response to anti-IL-5 therapy.Methods: In this retrospective multi-centre, real-life study, we analysed all SEA patients switched from anti-IL-5 to anti-IL-5Rα therapy due to inadequate response or intolerability. Pulmonary function tests, blood gas analyses, asthma control tests (ACT) and oral corticosteroid (OCS) usage were analysed and compared at three timepoints: baseline (BL, before anti-IL-5 therapy), timepoint 1 (T1, under anti-IL-5 therapy) and timepoint 2 (T2, under anti-IL-5Rα therapy).Results: Of 665 patients treated with anti-IL-5 antibodies, 70 were switched to anti-IL-5Rα and 60 were included in the analysis. Median treatment duration was 8 months [IQR 5; 15] for anti-IL-5 and 5 months [IQR 4; 6] for anti-IL-5Rα therapy. FEV1 was 61% of predicted at BL [IQR 41; 74], 61% [IQR 43; 79] at T1 and 68% [IQR 49; 87] at T2 (pT1-T2=0.011). ACT score was 10 [IQR 8; 13], 16 [IQR 10; 19] and 19 [IQR 14; 22], respectively (both p< 0.001). The number of patients requiring OCS was reduced from 41 (BL) to 32 (T1) and 19 (T2) (both p< 0.001). Ten patients discontinued anti-IL-5Rα therapy due to insufficient efficacy (n=7) and adverse events (n=3).Conclusion: Switching from anti-IL-5 to anti-IL-5Rα therapy in patients with inadequate response was associated with significantly improved FEV1, asthma control and OCS reduction.Keywords: benralizumab, eosinophils, mepolizumab, reslizumab, severe asthma